Bacterial synthesis of silicon/silica nanocomposites - Singh, Sanjay; Bhatta, Umananda M.; Satyam, P. V.; Dhawan, Alok; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2008)
The synthesis of silicon/silica nanoparticle composites by the bacterium Actinobacter sp. is demonstrated. More specifically, the formation of silicon/silica nanocomposite is shown to occur when the bacterium is exposed to K(2)SiF(6) precursor under ambient conditions. Based on the earlier reports where this bacterium has been shown to synthesize iron oxide and iron sulfide nanoparticles, it is hypothesized that this bacterium secretes reductases and oxidising enzymes, which lead to the Si/SiO(2) nanocomposite synthesis. The particles obtained by bacterial synthesis were thoroughly characterized. The cytotoxicity studies revealed that the particles do not display any cytotoxicity to human skin cells. The synthesis of silica nanoparticles by bacteria in the present study demonstrates the versatility of the organism, and the formation of elemental silicon by this environmentally friendly process expands further the scope of microorganism based nanomaterial synthesis.